Analisis Efisiensi Kinerja Heat Exchanger Tipe Shell and Tube Berdasarkan Parameter Laju Alir dan Fouling Factor - Malani, Salwa; Hasannah, Cintiya Septa (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The purpose of this study is to determine the results of the evaluation of shell and tube type heat exchanger performance efficiency based on flow rate parameters and fouling factors. In the evaluation of Heat Exchanger (HE-105) performance, two types of data collection were carried out, namely primary data collection used for basic analysis of Heat Exchanger (HE-105) performance evaluation at refinery facilities at PT X and secondary data collection was carried out as a calculation step in the evaluation of Heat Exchanger (HE-105) performance. The results showed that the actual average Rd (fouling factor) value of 0.0012 kcal/m2 hr C is which greater than the design Rd, this is due to the accumulated fouling. The average value of efficiency in the design is 98.41%, and the actual efficiency is 86.29%. The actual average efficiency value is smaller than the design average efficiency value, this is due to the influence of the high flow rate which causes the contact time between temperatures to decrease. However, the average efficiency value is still relatively high, indicating that the Heat Exchanger (HE-105) is still very feasible to use.